Caregiving burdens, depression levels, and related factors of attendants who care physical treatment and rehabilitation patients who applied to Turgut Ozal Medical Center - Yilmaz, Ramazan Cihad; Gunes, Gulsen (Annals of Medical Research, 2021)
Aim: The aim of this study was to evaluate the caregiving burden, depression and related factors of the caregivers of chronic patients who received physical therapy. Materials and Methods: Research was conducted as a cross-sectional descriptor. The sample of the study included 129 people who met the criteria for participation in the study and who applied to Turgut Özal Medical Center between 1 March 2018 and 1 March 2019, and cared for physical therapy and rehabilitation patients. Data was collected by using The Patient Information Form, Personal Care Form, Zarit Burden Interview (ZBI) and, Beck Depression Inventory (BDI), which were prepared by the researcher. Results: The mean of the caregiving burden was found to be as 38.48 ± 12.68, and the mean depression score as 13.68 ± 9.41. These values indicate that the caregiving burden is low-moderate and the depression score is mild. There was a significant positive correlation between the scores obtained from ZBI and the scores obtained from BDI (r:0.782, p<0.001). In the study, it was determined that factors such as age, gender, marital status, degree of proximity, income level, getting help, caregiving break, the presence of chronic disease of the caregiver affect the caregiving burden and depression level. It has been observed that some features of the patients affect the care burden and depression scores. Conclusion: As a result of the study, it was determined that the level of depression increased as the caregiving burden increased. A positive relationship was found between the caregiving burden and depression. It is advisable to arrange training and consultancy programs for caregivers to deal with the problems they face and to monitor caregivers at regular intervals.